The Analysis and Translation of Viewpoint in News Texts - Bayrak, Murat (Bandırma Onyedi Eylül Üniversitesi, 2025)
Pre-translation analysis of a text is highly significant before the translation process, particularly when translating news texts. News texts are typically viewed as instructive and informative types of writing. Their primary purpose is to convey current events to readers in an impartial, accurate, and timely manner. Therefore, non-commentary news texts should be devoid of personal opinions, and the information presented must be verifiable and precise. The language used is primarily official and formal, and verification is conducted through various sources to enhance the accuracy of the news. The main and well-known principle for presenting a news text is to answer the “5W and H questions,” which are “who, what, when, where, why, and how,” to avoid personal interpretation. Considering journalistic ethics and professional principles in news texts, a news translator should also pay attention to these features during the translation process. This requires careful and attentive reading to identify potential biases or subjective viewpoints. The purpose of this study is to underline the importance of understanding the features of news texts, the aspects translators should consider when translating news texts, and the significance of conducting a pre-translation analysis regarding viewpoint in news text translation. It has been suggested that due to the complex nature of news, it may be challenging to detect bias in terms of viewpoint; therefore, several key considerations and solutions for translation challenges are presented for the news translator in this study.

Çeviriye başlamadan önce bir metnin çeviri öncesi analizinin yapılması, özellikle haber metinlerinin çevirisinde, büyük önem taşımaktadır. Haber metinleri genellikle öğretici ve bilgilendirici yazı türleri olarak değerlendirilir. Bu tür metinlerin öncelikli amacı güncel olayları tarafsız, doğru ve zamanında okuyuculara aktarmaktır. Bu nedenle, yorum içermeyen haber metinleri kişisel görüşleri habere dâhil etmemeli, sunulan bilgiler doğrulanabilir ve kesin olmalıdır. Kullanılan dil genellikle resmi bir tonda olmalı ve haberin doğruluğunu artırmak için çeşitli kaynaklar aracılığıyla doğrulama yapılmalıdır. Bir haber metninin iletilmesinde kişisel yorumlardan kaçınmak için benimsenen temel ilke, “kim, ne, ne zaman, nerede, neden ve nasıl” sorularını içeren “5N1K” sorularını yanıtlamaktır. Haber metinlerinde gazetecilik etiği ve meslek ilkeleri de göz önünde bulundurulduğunda, bir haber çevirmeninin de çeviri sürecinde bu hususlara dikkat etmesi gerekir. Bu durum, olası ön yargıları veya öznel bakış açılarını tespit etmek için dikkatli ve özenli bir okuma gerektirir. Bu çalışmanın amacı, haber metinlerinin özelliklerini anlamanın önemini, çevirmenlerin haber metinlerini çevirirken göz önünde bulundurması gereken hususları ve haber metni çevirisinde bakış açısına ilişkin çeviri öncesi bir analiz yapmanın önemini vurgulamaktır. Haberlerin karmaşık doğası nedeniyle, bakış açısı açısından ön yargıyı tespit etmenin zor olabileceği göz önünde bulundurularak, haber çevirmenleri için çeviri zorluklarına yönelik bazı temel hususlar ve çözümler sunulmuştur.
Haber Metinlerinde Bakış Açısı Analizi ve Çevirisi
Keywords: Translation and Interpretation Studies; Çeviri ve Yorum Çalışmaları [EN] Translation Studies; Çeviribilim